Analisis Makna Character Building pada Perilaku Nabi Muhammad dalam Surat Al-Mukminun [23] ayat 1-11 - Ritonga, Muhammad Soleh (Fakultas Dakwah dan Ilmu Komunikasi, Universitas PTIQ Jakarta, 2021)
Character building must follow the example of the Prophet Muhammad. Because he is the incarnation of the Al-Qur'an, a human being who is successful in his life in the world with the various problems he faces and the several professions he does. Allah gave him success in this world and the hereafter. We can see this in Surah al-Mukminun verses 1-11. There, the tips for becoming a successful person are explained by implementing the characters implied in these verses. The first character that must be possessed is a religious personality. The second personal character is focused on concentration, praying seriously '. This prayer is like the head of all deeds. If the prayer is good, other deeds will be good, but if the prayer is not good, it will also affect the unworthiness of the other deeds. After prayer there is a character of discipline by keeping away from useless things that are not useful, be it deeds or words. then the character of obedience in paying zakat, shows a sense of social or caring. Then the personal character who is responsible by maintaining self-respect by using the available facilities in a halal way. Furthermore, a personal character that is trustworthy, the importance of maintaining trust and promise is a form of character of a person who can be trusted. And lastly is a consistent character, maintaining prayers regularly and working hard, istiqamah which shows that the person is able to be consistent in maintaining goodness. According to Al-Mâwardiy, carrying out these characters results in success in any field, be it education, economy, profession and so on. Even lasting success will be found in the afterlife.